2012
DOI: 10.1590/s0102-36162012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Localização segura na colocação dos pinos percutâneos no calcâneo

Abstract: Objective: To determine the areas presenting risk in six zones of the calcaneus, and to quantify the risks of injury to the anatomical structures (artery, vein, nerve and tendon). Method: Fifty--three calcanei from cadavers were used, divided into three zones and each subdivided in two areas (upper and lower) by means of a longitudinal line through the calcaneus. The risk of injury to the anatomical structures in relation to each Kirschner wire was determined using a graded system according to the Licht classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Structures contained within the tarsal tunnel, which are close to the medial region of the calcaneus, are vulnerable to injury caused by pins, drill bits or screws that penetrate the medial cortex of the calcaneus. 15 Albert et al 17 divided the calcaneus into three zones. Zone I starts at the calcaneocuboid joint and extends posteriorly as far as Gisane's critical angle; zone II starts at Gisane's angle and extends posteriorly to include all of the posterior facet; and zone III encompasses the posterior tuberosity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Structures contained within the tarsal tunnel, which are close to the medial region of the calcaneus, are vulnerable to injury caused by pins, drill bits or screws that penetrate the medial cortex of the calcaneus. 15 Albert et al 17 divided the calcaneus into three zones. Zone I starts at the calcaneocuboid joint and extends posteriorly as far as Gisane's critical angle; zone II starts at Gisane's angle and extends posteriorly to include all of the posterior facet; and zone III encompasses the posterior tuberosity.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that pins placed in the subchondral bone of the posterior facet or anterior to Gisane's critical angle might increase the risk of injury to the medial structures of the calcaneus. Labronici et al 15 demonstrated that division into six zones was more reproducible, with their respective risks of injury to the anatomical structures. The risk of injury can be quantified through the law of addition of probabilities, and this allows better planning with regard to the sites of lower risk for pin placement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations